The real-life management of overactive bladder: Turkish Continence Society multicenter prospective cohort study with short-term outcome - TARCAN, TUFAN (WILEY, 2019)
Introduction Turkish Continence Society aimed to analyze how overactive bladder (OAB) is being managed in routine practice by the urologists in Turkey. Material and methods Fourteen urology departments were randomly selected to represent the whole population in this multicenter study. An online data entry and storage software was created for patient recruitment and data assessment. A survey including demographic data, daily habits, lower urinary tract symptoms, and Turkish-validated OAB-V8 and ICIQ-SF questionnaires were completed by all patients. Second part of the survey, including the questions about clinical evaluation and management of the patient, was completed by the treating physician. Results A total of 507 patients (394 female and 113 male) were included. Behavioral therapy was recommended to 73.2% of female and 81.4% of male patients although bladder diary was requested for 59.5% and 52.7% of the female and male patients, respectively. In the first visit, 86.1% of the female and 89.3% of the male patients were given antimuscarinics (P = .431). Antimuscarinic-related side effects occurred in 94.9% and 88.9% of the female and male patients, respectively (P = .937). However, the rate of medical treatment change due to antimuscarinic-related side effects was only 1.7% in female and 4.8% in male patients at the end of 4 months. Conclusions Behavioral therapy and antimuscarinics were the preferred initial treatment modalities of OAB in concordance with the guidelines. Despite guideline recommendations, bladder diaries were not utilized in half of the patients. Insufficient efficacy appeared to be the main reason for treatment modification.
Keywords: management; multicenter; overactive bladder; study; URINARY-TRACT SYMPTOMS; ANTIMUSCARINIC THERAPY; BEHAVIORAL-THERAPY; INCONTINENCE; TERMINOLOGY; DRUG